2011
DOI: 10.1038/cddis.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Serine/threonine protein phosphatase 6 modulates the radiation sensitivity of glioblastoma

Abstract: Increasing the sensitivity of glioblastoma cells to radiation is a promising approach to improve survival in patients with glioblastoma multiforme (GBM). This study aims to determine if serine/threonine phosphatase (protein phosphatase 6 (PP6)) is a molecular target for GBM radiosensitization treatment. The GBM orthotopic xenograft mice model was used in this study. Our data demonstrated that the protein level of PP6 catalytic subunit (PP6c) was upregulated in the GBM tissue from about 50% patients compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
(44 reference statements)
3
34
0
Order By: Relevance
“…35 Using a DNA-PK kinase assay and assessing the phosphorylation status of replication protein A 2, a previous study demonstrated IR-induced DNA-PK activity in glioblastoma cell lines. 36 This increased activity was correlated with the survival fraction of those cells after a 5-Gy dose of irradiation, which suggests the role of DNA-PK in radiation resistance. 36 Furthermore, different studies have demonstrated the efficacy of its inhibition in promoting radio-sensitization of glioblastoma by inducing autophagy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…35 Using a DNA-PK kinase assay and assessing the phosphorylation status of replication protein A 2, a previous study demonstrated IR-induced DNA-PK activity in glioblastoma cell lines. 36 This increased activity was correlated with the survival fraction of those cells after a 5-Gy dose of irradiation, which suggests the role of DNA-PK in radiation resistance. 36 Furthermore, different studies have demonstrated the efficacy of its inhibition in promoting radio-sensitization of glioblastoma by inducing autophagy.…”
Section: Discussionmentioning
confidence: 86%
“…36 This increased activity was correlated with the survival fraction of those cells after a 5-Gy dose of irradiation, which suggests the role of DNA-PK in radiation resistance. 36 Furthermore, different studies have demonstrated the efficacy of its inhibition in promoting radio-sensitization of glioblastoma by inducing autophagy. 37 In conclusion, considering the important impact of MSI1 on DNA repair, radio-resistance, and other cancer-relevant processes, 13 MSI1 targeting can prove to be an important avenue for the treatment of glioblastoma patients when combined with radiotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…PP6 regulates the activities of many host proteins (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and it is therefore possible that PP6 silencing perturbs the virus life cycle by affecting other cellular processes. However, the fact that PP6 interacts directly with the viral RdRP suggests that it plays a direct role in the viral life cycle by regulating the posttranslational modifications of viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PP6 is a member of the PP2A subfamily of protein phosphatases, cellular enzymes that catalyze the liberation of inorganic phosphate from proteins and peptides at serine or threonine residues (22). PP6 is a significant regulator of a number of cellular processes, including chromosome stability and the DNA damage response (23)(24)(25)(26)(27), mitosis and the regulation of cell cycle progression (22,(28)(29)(30)(31), signaling (32,33), pre-mRNA splicing (34), and vesicular trafficking (35). The catalytic subunit PPP6C and the regulatory subunits PPP6R1 and PPP6R3 were found to copurify with the viral RdRP.…”
mentioning
confidence: 99%
“…PP6 consists of a catalytic subunit, PP6c, and regulatory molecules including SAPS1, -2 and -3. PP6 is mainly expressed in lymphoid, cardiac, and neuronal cells (31)(32)(33). SIT4, a yeast homolog of PP6, was identified as a molecule required for the G 1 to S transition of the cell cycle (34).…”
mentioning
confidence: 99%